2018
DOI: 10.1111/var.12156
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance, Translation, Enculturation: Necessary Research in New Media, Technology, and the Senses

Abstract: This article examines a research program centered at the nexus of five seemingly unrelated fields: art practice with new technologies, anthropology, cultural studies of technology, the development of new technologies that seek to make new forms of sensation, and Indigenous new media studies. First, I articulate a broader area of interdisciplinary research called sensory studies. Subsequently, and switching to the pronoun "we," I briefly describe the aims of Sensory Entanglements: a collaborative research progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…is contextual and personalized information provides the data foundation for learning analytics. At the same time, the intelligent assistant provides the support of the domain knowledge base at the system level, and a large-scale, highquality domain knowledge base is the key to realize the effective learning support function [15]. rough the data measurement and collection of learners and their learning situations, the obtained personalized data of learners can be used for effective learning analysis through data mining, atmosphere computing, affective computing, and other methods to understand and optimize learning and learning situations and facilitate the construction of more complete learner models.…”
Section: Introductionmentioning
confidence: 99%
“…is contextual and personalized information provides the data foundation for learning analytics. At the same time, the intelligent assistant provides the support of the domain knowledge base at the system level, and a large-scale, highquality domain knowledge base is the key to realize the effective learning support function [15]. rough the data measurement and collection of learners and their learning situations, the obtained personalized data of learners can be used for effective learning analysis through data mining, atmosphere computing, affective computing, and other methods to understand and optimize learning and learning situations and facilitate the construction of more complete learner models.…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that the cross and sculpture can represent some meanings in daily life. In fact, from a certain point of view, this is what we call a symbol [5]. The symbol in the development of art can be divided into three levels according to its own definition and development concept, namely, its own concept, abstract spirit, imagination, and association.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most migrants who visit Kampung Dukuh actually motivate the young generation of the Kampung Dukuh to change and enjoy modernity like society in general [26]. So that the pattern of enculturation has changed into a pattern of acculturation (even assimilation) in cultures where they are indigenous people trying to release the cultural heritage they have and shift to the values and behavior of a more modern society in this case immigrants [27].…”
Section: Introductionmentioning
confidence: 99%